Shear strength of reinforced fly-ash-based geopolymer concrete beams with and without shear reinforcement. (April 2023) - Shibayama, Atsushi; Nishiyama, Minehiro
Abstract: Geopolymer concrete (GPC) has attracted significant attention as an eco-friendly material and various studies have been conducted at the material level. However, studies on their structural properties are limited. In this study, shear tests were conducted on 10 fly-ash-based GPC beams subjected to double-curvature bending to understand the shear properties of GPC beams. The experimental parameters were the shear span ratio, concrete strength, and transverse shear reinforcement ratio. The shear cracking and ultimate shear strengths of GPC beams increase as the shear span ratio decreases. Existing design equations for shear cracking and shear ultimate strengths can be applied to GPC beams. The applicability and accuracy of existing shear ultimate strength evaluation equations, including existing experimental results, were verified, and the Architectural Institute of Japan design equation was found to be the most applicable, regardless of the loading arrangement and shear span ratio.